DIFFERENCES IN PRIMARY MENSTRUAL PAIN INTENSITY BEFORE AND AFTER GIVING TURMERIC MEDICINE TO ADOLESCENT GIRLS - Noviyanti, Putu Risma; Erawati, Ni Luh Putu Sri; Mahayati, Ni Made Dwi (International Conference on Multidisciplinary Approaches in Health Science, 2025)
Â  Background: One of the problems experienced by adolescents, especially female adolescents, is menstrual pain. Menstrual pain management can be done with non-pharmacological methods, one of which is the administration of turmeric loloh. The purpose of this study was to determine the difference in the intensity of primary menstrual pain before and after the administration of turmeric loloh in female adolescents girls. Method: The research method used was a pre-experiment with a one-group pretest-posttest design. The sample size used was 20 female adolescents selected by purposive sampling. Pain intensity assessment was carried out using a numeric rating scale (NRS). Research data were taken with the intensity of primary menstrual pain before and after administration of turmeric loloh for two days as much as 150 ml in the morning and evening. Bivariate analysis used the Wilcoxon test with Î± <0.05. Result: The results of the menstrual pain intensity score before the administration of turmeric loloh showed a median value of 5 and after the administration of turmeric loloh there was a decrease in the median value of 2 with a Ï value of 0.00 <Î± (0.05) and a Z value of -3.970. Conclusion: In conclusion, there is a significant difference in the intensity of primary menstrual pain in adolescent girls before and after administration of turmeric loloh. Turmeric loloh is recommended for adolescent girls as a non-pharmacological alternative to reduce the intensity of primary menstrual pain.